2007
DOI: 10.1002/acp.1376
|View full text |Cite
|
Sign up to set email alerts
|

Eyewitness memory following discussion: using the MORI technique with a Western sample

Abstract: Researchers studying memory conformity have made significant advances in our understanding of the phenomenon, but have used methods with significant shortcomings. Mori's three-stage method addresses many of these concerns. To date the technique has not been replicated on a Western sample. We present such a study, and discuss two significant improvements to Mori's method. We found that subjects were more likely to report the correct answer for non-discussed critical details than discussed critical details. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
125
1
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(147 citation statements)
references
References 24 publications
14
125
1
7
Order By: Relevance
“…In accordance with previously demonstrated results (e.g., Gabbert et al, 2001;Garry et al, 2008;Wright et al, 2000), it was hypothesized that individuals who discussed the event with a co-witness who had seen a different version of the video would show less accurate memory than those in the natural discussion groups or those who did not discuss the event.…”
Section: Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…In accordance with previously demonstrated results (e.g., Gabbert et al, 2001;Garry et al, 2008;Wright et al, 2000), it was hypothesized that individuals who discussed the event with a co-witness who had seen a different version of the video would show less accurate memory than those in the natural discussion groups or those who did not discuss the event.…”
Section: Methodssupporting
confidence: 75%
“…Because the participants were unaware that they had seen different stimuli, their interactions with the group were likely to be more natural than those of delegated confederates. This methodology has been used in several studies of the effects of co-witness discussion on memory (e.g., Gabbert, Memon, & Allan, 2003;Garry, French, Kinzett, & Mori, 2008;Paterson, Kemp, & Ng, 2009;Wright, Self, & Justice, 2000). These studies have largely confirmed the results of studies using confederates, finding that participants who viewed different versions of the video erroneously recalled items from the alternative version of the stimulus when later giving their individual accounts.…”
mentioning
confidence: 71%
“…On subsequent individual recall and recognition tests, participants often incorporate the confederates' errors into their own memory reports, a process termed the social contagion of memory. Research in the related, memory conformity paradigm has also demonstrated the powerful effect of social influence on false memory (Allan & Gabbert, 2008;Bodner, Musch, & Azad, 2009;Gabbert, Memon, & Allan, 2003;Gabbert, Memon, Allan, & Wright, 2004;Gabbert, Memon, & Wright, 2006Garry, French, Kinzett, & Mori, 2008;Skagerberg & Wright, 2008a, 2008bWright, Gabbert, Memon, & London, 2008;Wright, Self, & Justice, 2000).…”
mentioning
confidence: 99%
“…Other studies have explored variations of OP by having adult participants receive information directly from a co-witness, instead of implying what a co-witness had allegedly said, showing various decreases in memory accuracy after witnesses have been exposed to co-witness information (Garry, French, Kinzett, & Mori, 2008;Roediger, Meade, & Bergman, 2001;Skagerberg & Wright, 2008). Merckelbach, Van Roermund, and Candel (2007) found that having a confederate deny true information was just as powerful as providing misinformation during a collaborative recall study.…”
Section: Literature Reviewmentioning
confidence: 99%